School control of information, advice and guidance during transition: a two year study into post-16 student decision-making - Garforth, Graham (2016)
The majority of research into choice, transition and decision-making took place in the 1990s-2000s. Since this time the context in which post-16 transition takes place has been changing due to increased competition between institutions and the extended length of time students are required to remain in education or training through raising the participation age. Additionally, in 2012 the government made schools responsible for Information, Advice and Guidance.